2022
DOI: 10.1103/physrevb.105.064421
|View full text |Cite
|
Sign up to set email alerts
|

Probing the tunability of magnetism with external pressure in metastable Sr2NiIrO6 double perovskite

Abstract: In Sr 2 NiIrO 6 long-range Ir-Ir antiferromagnetic exchange interactions have been reported to overcome the ferromagnetic Ni-Ir interactions hampering the otherwise expected ferromagnetic behavior. Prompted by this, a combination of x-ray absorption spectroscopy and x-ray diffraction at high pressure is used here to investigate the interplay between the magnetic structure of the Ir sublattice and lattice degrees of freedom. The compression of Sr 2 NiIrO 6 drives an unexpected nonmonotonic change of the x-ray m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…82 Their linear fittings yield positive Θ Weiss values of 42 K (50 Oe), 51 K (500 Oe), and 49 K (5 kOe), which indicates the predominance FM/FiM interactions above T C . We also observed that the frustration factor, defined as f frus = |Θ Weiss |/T C , 83 yields f frus = 0.65, 0.78, and 0.75, respectively. Theses values are less than 1 and indicate that the system is not geometrically frustrated.…”
Section: Structural and Surfacementioning
confidence: 56%
“…82 Their linear fittings yield positive Θ Weiss values of 42 K (50 Oe), 51 K (500 Oe), and 49 K (5 kOe), which indicates the predominance FM/FiM interactions above T C . We also observed that the frustration factor, defined as f frus = |Θ Weiss |/T C , 83 yields f frus = 0.65, 0.78, and 0.75, respectively. Theses values are less than 1 and indicate that the system is not geometrically frustrated.…”
Section: Structural and Surfacementioning
confidence: 56%